Characterization of kindlin3 in Integrin functions - Feng, Chen (2013)
Integrins are heterodimeric cell adhesion molecules that are involved in many biological processes. Integrin ligand-binding requires its activation by the FERM (4.1 ezrin radixin moesin)-domain-containing cytoplasmic protein talin 1/2. Recently, another family of FERM-domain-containing cytoplasmic proteins known as kindlins has been shown to regulate talin-induced integrin conformation change and activation. The primary focus in this study is kindlin3, which is expressed in platelets, hematopoetic cells and endothelial cells. In the disease known as leukocyte adhesion deficiency (LAD) III, mutation(s) in KINDLIN3 disrupts kindlin3 expression, leading to defective alpha2 integrins-mediated leukocyte adhesion and integrin alphaIIbbeta3-mediated platelet aggregation. LADIII patients therefore have a compromised immune system and show bleeding disorders. Although kindlin3 is well-established to be important in integrin ligand-binding, little is known of its role in integrin outside-in signaling, a process that is essential for integrin-mediated cell spreading and migration. In this study, we identified a novel interaction between kindlin3 and receptor for activated-C kinase 1(RACK1). This interaction is dependent on the pleckstrin homology (PH) domain of kindlin3. We also provide evidence that integrin alpha2 cytoplasmic tail, kindlin3 and RACK1 can potentially form a ternary complex. Kindlin3 and RACK1 localize to the lamellipodium of migrating T cells on integrin alphaLbeta2 ligand intercellular adhesion molecule-1 (ICAM-1). This was also observed in HUVECs spreading on integrin alpha5beta1 ligand fibronectin in which kindlin3 and RACK1 localized to the cell’s leading edge. An interesting observation in HUVECs is that kindlin3 did not localize to mature focal adhesion sites. Rather kindlin3 appears to be important in nascent adhesion sites that contain cytoplasmic proteins necessary for direction sensing, for example RACK1, and possibly protein translational machineries.